Graphenylene, a unique two-dimensional carbon network with nondelocalized cyclohexatriene units - Song, Qi; Wang, Bing; Deng, Ke; Feng, Xinliang; Wagner, Manfred; Gale, Julian D.; Muellen, Klaus; Zhi, Linjie (Journal of Materials Chemistry C, 2013)
Over many years chemists have established the general principle that two-dimensional chemical structures constructed with pure sp2-carbon atoms will definitely form an aromatic system with delocalized electron density. However, based on a recently proposed chemical structure, graphenylene, this rule may finally be broken. Herein, we predict the properties of a new two-dimensional sp2-carbon network known as graphenylene, which is the first example of a non-delocalized sp2-carbon structure composed of cyclohexatriene units with two quite distinct C-C bonds within a C6 ring. In addition, theoretical calculations demonstrate that graphenylene has periodic pores of 3.2 Å in diameter and is a semiconductor with a narrow direct band gap, making it promising for various applications, such as electronic devices and efficient hydrogen separation. This study provides a new perspective on carbon allotropes, leading to a better understanding of [N] phenylene based organic frameworks, as well as clarifying the relationship between benzene and cyclohexatriene. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20